GIBAH (INTERNAL INITIATIVE MOVEMENT PROGRAM FOR GRANTS): A VIABLE IMPLEMENTATION OF MBKM PROGRAM IN SCIENCE MAJOR AT UNIVERSITAS KRISTEN MARANATHA - Robby Yussac Tallar; Maya Malinda; Olga Pattipawaej; Prabu Madvi H.A.S (European Journal of Humanities and Educational Advancements, 2021)
Since 2020 the Indonesian government has issued an MBKM program that has changed the paradigm of the education system, especially universities in Indonesia. Universitas Kristen Maranatha certainly quickly grasped the intent of the government’s policy through the MBKM program by changing its education system. Lecturers and students are expected to play an active role and receive grants from various areas of the MBKM program offered by both the government and universities. Several policies from Universitas Kristen Maranatha that support MBKM activities have been stated in several related decrees, including the Decree on the Research Scheme in Universitas Kristen Maranatha, one of which reads that research lecturers must involve students in every proposed research grant program, including in the exact field. Joint involvement between lecturers and students in obtaining grants in the MBKM program, especially in science major, is considered to still need to be improved so that universities through LPPM take the initiative to carry out a moral action called GIBAH (Internal Initiative Movement Program for Grants). The question addressed that arises in this study are whether this movement has been going well by knowing how much students are involved in it. Therefore, the purpose of this research is to obtain complete existing information as well as an accurate measurement of the GIBAH moral action that has been carried out. The research analysis is divided into several parts, namely situational analysis/level of understanding, socialization analysis, and analysis of the success/implementation of action research that has been achieved. The results showed that the awareness of both lecturers and students were increased significantly during pandemic COVID-19 through several MBKM programs at Universitas Kristen Maranatha.